Harnessing Value Transmission to Enhance Salesperson Performance and Relationships - Simamora, Elisabeth Rotua (Universitas Semarang, 2025)
The company capable of winning the competition is the company that becomes the choice for the customers. The success of a company in getting a reference on a customer's mind, thus resulting in purchasing actions carried out by customers must be distinct from the company's efforts to know what its priorities on customer desires and give them the best of their needs. One thing that supports this company's success is the management of the sales force. In improving sales force performance, each sales force must have expertise on adapting by digging information about the needs of buyers, own cognitive intelligence and knowledge of product goods. This research highlights the contradictory relationship between relational capabilities on performance power sales. The objective of this study is to analyze variable Value Transmission Effectiveness, which are expected to resolve the contradiction between relational capability and sales performance. A distribution sample was given to Power Seller Pharmacy using a purposive sampling technique. The testing model and hypothesis use an equality analysis model (Structural Equation Model-SEM) with AMOS software